Feasibility of the Montreal Cognitive Assessment in acute stroke patients - Horstmann, Solveig; Rizos, Timolaos; Rauch, Geraldine; Arden, Cathrin; Veltkamp, Roland (European journal of neurology, 2014)
BACKGROUND AND PURPOSE: Cognitive deficits are common following stroke. Cognitive function in the acute stroke setting is a predictive factor for mid-term outcome. The Montreal Cognitive Assessment (MoCA) is a screening tool for cognitive impairment. The feasibility of MoCA in the acute phase of stroke was evaluated and factors predictive of cognitive impairment were determined. - METHODS: In this prospective, single-centre, explorative and observational study consecutive patients with ischaemic (IS) or haemorrhagic (ICH) stroke were enrolled between March 2011 and September 2012. The routine work-up for each patient encompassed assessment of cardiovascular risk factors, the National Institutes of Health Stroke Scale (NIHSS) and the pre-morbid modified Rankin Scale (mRS) score. Cognitive performance was measured using the German version of the MoCA within the first days of admission. A MoCA score of <26 was considered to indicate cognitive impairment. - RESULTS: Between March 2011 and September 2012 a total of 842 patients with IS (89.0%) and ICH (11.0%) were enrolled in our study. MoCA was feasible in 678/842 patients (80.5%). Factors independently associated with non-feasibility were stroke severity (NIHSS), pre-morbid functional status (mRS), age and lower educational level. Mean MoCA was 21.4 (SD 5.7). A total of 498/678 (73.5%) patients appeared cognitively impaired (<26/30). Independent predictive factors for a lower MoCA score were age, educational level, stroke severity (NIHSS) and pre-morbid functional status (mRS). - CONCLUSIONS: In the acute phase of stroke, MoCA is feasible in about 80% of eligible patients. At this stage, MoCA identifies a cognitive impairment in 75% of patients.
Gesehen am 04.02.2021